Moral reasoning and moral identity in lawyers dedicated to arbitration - Villalba Garcés, Jorge (2021)
Arbitration offers a fast and effective way to resolve disputes between different entities. Arbitrators have the responsibility to solve these conflicts with justice and impartiality. Given the importance of this function, it is necessary to have professionals who have developed their moral capacities to the fullest extent. Unfortunately, various acts of corruption have cast doubt on the moral capacity of some arbitrators and have highlighted the need to investigate the moral development of this population. In this context, the present study aimed to describe and analyze the characteristics of moral reasoning and moral identity of a group of lawyers who devote a good part of their professional work to arbitration. Seventeen lawyers, men and women, who devote more than 50 % of their time to arbitration, participated in this study. The results indicate that, generally speaking, participants reason at a conventional level that makes them prioritize interpersonal expectations and the maintenance of the social system over moral principles. Additionally,the interviewees show different types of identities, some related to social or prosocial issues, but none strictly moral. The results are discussed emphasizing the consequences of low moral reasoning and poor moral identity development, and the need to rethink the moral education of students in law schools.